The astonishing adventures of Fanboy and Goth Girl - Lyga, Barry (Graphia, 2007)
A fifteen-year-old "geek" who keeps a list of the high school jocks and others who torment him and pours his energy into creating a great graphic novel, encounters Kyra, Goth Girl, who helps change his outlook on almost everything, including himself